Genetic population data from Araraquara region (SP State, Brazil) using PowerPlex® 16 Systems - Martins, Joyce Aparecida [UNESP]; Paneto, Greiciane Gaburro [UNESP]; Pereira, Gabriella Augusto [UNESP]; Lima, Maria Jenny Mitraud; de Santi Alvarenga, Vera Lucy [UNESP]; Cicarelli, Regina Maria Barretto [UNESP] (Elsevier, 2006)
In the present study, allele frequency distributions for the 15 STR loci included in the PowerPlex® 16 Systems (Promega) were obtained from a sample of 55 unrelated individuals living in Araraquara region (SP, Brazil). The frequency of each allele for each locus tested, the exact test and the forensic and paternity parameters were calculated using POWERSTATS ver. 1.2 (Promega) and GENEPOP ver. 3.2 software. All loci are in the Hardy-Weinberg equilibrium and they reached a combined power discrimination of 0.999999999999999973 and combined power exclusion of 0.99999987, showing to be a powerful tool for paternity testing and individual identification in the population analyzed. © 2005 Elsevier B.V. All rights reserved.
Keywords: Brazil; Population data; STR